Robo-Eroticism: Designing Desire via Creativity in Sexual Robots - Harillo Pla, Adrià (Conatus - Journal of Philosophy, 2025)
In this article, I argue that the integration of creativity into the development of sexual robots is a vital and indispensable factor for their widespread acceptance and functionality. I contend that creativity serves as a linchpin in the realization of fully functional sexual robots. To substantiate this assertion, I present four key stages. In the first stage, I offer an in-depth analysis of the contemporary state-of-the-art in sexual robots, encompassing both their current practical implementations and the theoretical foundations that underpin them. The second stage delves into the intricate connection between sexuality and creativity, drawing on diverse case scenarios that exemplify the interdependence of these domains as a condition of possibility. The third stage underscores the paramount importance of creativity in the design and development of sexual robots, elucidating its strategic role in securing broad societal acceptance. In the fourth and final stage, I discuss the imperative need to establish a new interdisciplinary field of study, which I propose to term “Robo-Eroticism.” This domain promises to comprehensively explore the fusion of technology and human sexuality from a creative perspective. By traversing these four stages, this article unveils the pivotal role of creativity in shaping the future evolution of sexual robots.